Galanin regulates prolactin release and lactotroph proliferation - Wynick, David (The National Academy of Sciences, 1998)
The neuropeptide galanin is predominantly expressed by the lactotrophs (the prolactin secreting cell type) in the rodent anterior pituitary and in the median eminence and paraventricular nucleus of the hypothalamus. Prolactin and galanin colocalize in the same secretory granule, the expression of both proteins is extremely sensitive to the estrogen status of the animal. The administration of estradiol-17β induces pituitary hyperplasia followed by adenoma formation and causes a 3,000-fold increase in the galanin mRNA content of the lactotroph. To further study the role of galanin in prolactin release and lactotroph growth we now report the generation of mice carrying a loss-of-function mutation of the endogenous galanin gene. There is no evidence of embryonic lethality and the mutant mice grow normally. The specific endocrine abnormalities identified to date, relate to the expression of prolactin. Pituitary prolactin message levels and protein content of adult female mutant mice are reduced by 30–40% compared with wild-type controls. Mutant females fail to lactate and pups die of starvation/dehydration unless fostered onto wild-type mothers. Prolactin secretion in mutant females is markedly reduced at 7 days postpartum compared with wild-type controls with an associated failure in mammary gland maturation. There is an almost complete abrogation of the proliferative response of the lactotroph to high doses of estrogen, with a failure to up-regulate prolactin release, STAT5 expression or to increase pituitary cell number. These data further support the hypothesis that galanin acts as a paracrine regulator of prolactin expression and as a growth factor to the lactotroph.